التصوير الذاتي "السيلفي" وعلاقته بالحاجات في ضوء نظرية ماسلو لدى عينة من طلاب جامعة البعث - سويد، داليا (جامعة البعث, 2022)
هدفت الدراسة الحالية تعرف العلاقة بين التصوير الذاتي (السيلفي) وبين الحاجات النفسية حسب نظرية ماسلو لدى عينة من طلاب جامعة البعث. تكونت عينة البحث من 388 طالب وطالبة من جامعة البعث. استخدم في الدراسة مقياس التصوير الذاتي الذي وضعه (Balakrishnan & Griffiths, 2017) ومقياس الحاجات النفسية الذي وضعه (Lester,1990). أظهرت نتائج البحث أن 64% من أفراد العينة يقعون ضمن المستوى المتوسط في استخدام التصوير الذاتي، كما وجدت الدراسة أن أكثر الحاجات إلحاحا بين طلاب الجامعة هي الحاجات الفيزيولوجية تليها الحاجة للأمن ثم الحاجة إلى الانتماء وأقلها انتشارا هي الحاجة النتائج أيضا وجود علاقة إلى تقدير الذات والحاجة إلى تحقيق الذات. بينت ارتباطية موجبة دالة إحصائيا بين التصوير الذاتي وبين الحاجة إلى تقدير الذات وعلاقة سلبية دالة إحصائيا بين التصوير الذاتي والحاجة إلى الأمن بينما لا توجد علاقة ارتباطية بين التصوير الذاتي وبقية الحاجات. بينت الدراسة عدم وجود فروق دالة إحصائيا في سلوك التصوير الذاتي تعود لمتغير الجنس ولمتغير الاختصاص، بينما وجدت فروق دالة إحصائيا تعود لمتغير السنة الدراسية لصالح السنة الأخيرة. فيما يتعلق بالحاجات النفسية فلقد أظهرت النتائج وجود فروق دالة إحصائيا في الحاجات الفيزيولوجية لصالح الذكور، وفي الحاجة للانتماء لصالح الإناث. كما وجدت فروق دالة إحصائيا في الحاجات الفيزيولوجية والحاجة إلى الأمن لصالح الاختصاص التطبيقي بينما لا توجد فروق في بقية الحاجات. كما وجدت فروق في الحاجات الفيزيولوجية والحاجة إلى تقدير الذات لصالح طلاب السنة الأخيرة. The current study aims at investigating the relationship between selfie and the psychological needs according to Maslow's theory among a sample of Al-Baath University students. The research sample consisted of 388 male and female students from Al-Baath University. In the study, the scale of selfie developed by (Balakrishnan & Griffiths, 2017) and the psychological needs scale developed by (Lester, 1990) were used. The results of the research showed that 64% of the sample members fall within the average level in using the selfie. The study also found that the most prevalent needs among university students are the physiological needs, followed by the need for safety, then the need for belonging, and the least prevalent is the need for self-esteem and the need for self-actualization. The results also showed a positive, statistically significant correlation between the selfie and the need for selfesteem, and a negative, statistically significant relationship between the selfie and the need for security, while there was no correlation between the selfie and the rest of the needs. The study showed that there were no statistically significant differences in selfie due to the variable of sex and the variable of specialization, while there were statistically significant differences due to the variable of the school year in favor of the last year. With regard to psychological needs, the results showed that there were statistically significant differences in the physiological needs in favor of males, and in the need for belonging in favor of females. There were also statistically significant differences in the physiological needs and the need for safety in favor of the applied specialization, while there were no differences in the rest of the needs. There were also differences in the physiological needs and the need for self-esteem in favor of final year students.
Keywords: نظرية ماسلو -- التصوير الذاتي -- طلبة الجامعات -- الهواتف الذكية -- الصور الشخصية